Environmental impact assessment of horse and mechanical traction for vineyard cultivation - Laura Fiorani; Lucia Rocchi; Giuditta Meloni; Cesare Castellini (Italian Journal of Animal Science, 2024)
In the European Union, energy consumption in agriculture and forestry is less intense than in other economic sectors. However, fossil and non-renewable sources, particularly oil, are predominant, with higher percentages than in different economic sectors. In this context, this study aims to compare the environmental impact generated by equine and mechanical traction for viticulture practices in an organic production context, using life cycle assessment (LCA). Three scenarios were considered: business as usual (i.e., tractor-grown grapes) and horse-grown grapes but with two feeding options (tractor-grown hay and horse-grown hay). The results show that the tractor-grown grape scenario has higher impacts in five impact categories whereas the horse-grown scenario shows higher Global Warming, and to a minor extent Land use. Specifically, the worst results of the control scenario are in the mid-point category of Inorganic Respiratory due to fuel use, which produces P M 2.5. Fuel use is also the cause of the highest environmental burdens in other categories such as terrestrial Ecotoxicity. A sensitive analysis of the results was performed considering the endpoint damage categories. The outcomes show that, in general, the impact of horses is quite stable even under potentially different conditions. Some categories (ecosystem quality, global impact) are only slightly affected by variation in growth time, while all other categories (human health, resources, climate change) experience greater variation.